The Influence of Menu and Service Quality of Wedding Events and Guest Satisfaction at Le Polonia Hotel Medan - Annisa, Fitrah Ade (Jurnal Online Mahasiswa, 2023)
ABSTRACT Wedding events are one of the hotel’s efforts to increase revenue and guest occupancy. Wedding events are sacred events that are only held once in a lifetime and are expected to be held smoothly, but of course preparing for a wedding is not an easy task and requires several considerations, one of which is choosing what menu to serve and how it tastes. Because the menu that is served will create a first impression for the guests who attend or organize the event. Quality of service is very much needed for the smooth running of the wedding, unsatisfactory service and does not meet guest expectations will be able to affect guest satisfaction and service quality will be a consideration for prospective customers who want to hold a wedding. The purpose of this research is to find out how much influence the menu has on satisfaction guests and the quality of wedding event services on guest satisfaction at Le Polonia Hotel. This study uses a quantitative approach method. In the sampling technique, the researcher used a random sampling technique with a total of 40 samples. The author uses a Likert scale to measure the effect of menu and service quality on guest satisfaction. Keywords: Menu, Service Quality, Guest Satisfaction